Homogeneous cooling and heating states of dilute soft-core gases under nonlinear drag - Takada Satoshi (EPJ Web of Conferences, 2021)
The temperature evolution of dilute soft inertial gas-solid suspensions is theoretically analyzed when the gas particles are influenced by a nonlinear drag force from a background fluid. The kinetic theory is extended to this system, and the time evolutions of the temperature and the kurtosis of the velocity distribution are derived. Molecular dynamics simulations are also performed to check the validity of the theory, and they show good agreement with the theoretical predictions.